Homotopy Perturbation Method for Solving Wave-Like Nonlinear Equations with Initial-Boundary Conditions - Afgan Aslanov (Discrete Dynamics in Nature and Society)
The homotopy perturbation method is employed to obtain approximate analytical solutions of the wave-like nonlinear equations with initial-boundary conditions. An efficient way of choosing the auxiliary operator is presented. The results demonstrate reliability and efficiency of the method.